Climatic and landscape controls on effective discharge. Issue 20 (29th October 2015) - Basso, S.; Frascati, A.; Marani, M.; Schirmer, M.; Botter, G.
Abstract: The effective discharge constitutes a key concept in river science and engineering. Notwithstanding many years of studies, a full understanding of the effective discharge determinants is still challenged by the variety of values identified for different river catchments. The present paper relates the observed diversity of effective discharge to the underlying heterogeneity of flow regimes. An analytic framework is proposed, which links the effective ratio (i.e., the ratio between effective discharge and mean streamflow) to the empirical exponent of the sediment rating curve and to the streamflow variability, resulting from climatic and landscape drivers. The analytic formulation predicts patterns of effective ratio versus streamflow variability observed in a set of catchments of the continental United States and helps in disentangling the major climatic and landscape drivers of sediment transport in rivers. The findings highlight larger effective ratios of erratic hydrologic regimes (characterized by high flow variability) compared to those exhibited by persistent regimes, which are attributable to intrinsically different streamflow dynamics. The framework provides support for the estimate of effective discharge in rivers belonging to diverse climatic areas. Key Points: Identification of hydrologic and morphologic controls on effective discharge Analytic expression of the ratio between effective and mean discharge Flow regime (flow variability) explains the heterogeneity of observed effective discharges